2013
DOI: 10.1590/s1677-5538.ibju.2013.04.15
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Urolithiatic Effect of Cow Urine Ark on Ethylene Glycol-Induced Renal Calculi

Abstract: Purpose: To investigate the anti-urolithiatic effect of cow urine ark (medicinal distilled cow urine) on ethylene glycol (EG) induced renal calculi. Materials and Methods: 36 male Wistar rats were randomly divided into 6 equal groups. Group I animals served as vehicle control and received distilled water for 28 days. Group II to VI animals received 1% v/v EG in distilled water for 28 days. Group II served as EG control. Group III and IV (preventive groups) received cow urine ark orally for 28 days in doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…Von Kossa and H & E staining of kidney sections from diseased animals at the end of the 7th week were subjected to microscopic examination which confirmed that nephrolithic rats showed intratubular and interstitial crystal deposits consistent of other investigator findings (Khan et al, 2010;Shukla et al, 2013). The presence of such deposits is evidence of adhesion and retention of calcium oxalate crystal within the renal tubules.…”
Section: Discussionsupporting
confidence: 74%
“…Von Kossa and H & E staining of kidney sections from diseased animals at the end of the 7th week were subjected to microscopic examination which confirmed that nephrolithic rats showed intratubular and interstitial crystal deposits consistent of other investigator findings (Khan et al, 2010;Shukla et al, 2013). The presence of such deposits is evidence of adhesion and retention of calcium oxalate crystal within the renal tubules.…”
Section: Discussionsupporting
confidence: 74%
“…In the present study rats are used to evaluate calcium oxalate deposition in kidney owing to their close resemblance to the human urinary system. Selection of male rats in the present study was based on a previous study showing a higher rate of crystal depositions in male as compared to female rats [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies can be designed to its mechanism of action. (17) The GA is one of the ingredients of 'Panchagawya' which is capable of treating many curable as well as incurable diseases. It has been used in Ayurvedic preparations since time immemorial as cited in ancient holy texts like Sushruta Samhita, CharakaSamhita, Vridhabhagabhatt, Bhavaprakash, RajniGhuntu, Atharva Veda, Amritasagar, etc.…”
Section: Discussionmentioning
confidence: 99%